2006
DOI: 10.1051/ocl.2006.0016
|View full text |Cite
|
Sign up to set email alerts
|

Limitations extractives des ingrédients fonctionnels natifs : lipides bioactifs par modifications chimiques

Abstract: Phytosterols draw their origin from plants (oilcrops and cereals seeds, vegetables, fruits, nuts) Key words: lipids, phytosterols, chemical modification, industrial applicationLes stérols d'origine végétale, appelés aussi phytostérols, sont des molécules présentes chez tous les végétaux dans la nature. Ils possèdent des structures et des propriétés qui leur sont propres et qui déterminent leur activité biologique dans le monde du vivant. Depuis plusieurs années, ces molécules bioactives, encore peu exploitée… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
4
0
2
Order By: Relevance
“…Philips et al and Lechner et al found a quantity of total sterols between 2970 and 3600 mg/kg in crude soybean oil, and 3500 mg/kg in crude sunflower oil. The study of Mouloungui et al and Roche et al supported the conclusions stated above. The sterols were present in rapeseed oil in greater quantity (7000 mg/kg against 4050 and 3230 mg/kg in sunflower and soybean oils, respectively).…”
Section: Impact Of the Crushing Process On The Micronutrient Content supporting
confidence: 54%
See 1 more Smart Citation
“…Philips et al and Lechner et al found a quantity of total sterols between 2970 and 3600 mg/kg in crude soybean oil, and 3500 mg/kg in crude sunflower oil. The study of Mouloungui et al and Roche et al supported the conclusions stated above. The sterols were present in rapeseed oil in greater quantity (7000 mg/kg against 4050 and 3230 mg/kg in sunflower and soybean oils, respectively).…”
Section: Impact Of the Crushing Process On The Micronutrient Content supporting
confidence: 54%
“…Adapted from Rodriguez‐Acuna et al, Evrard et al , Roche , Zacchi and Eggers , Pregnolato et al , Gutfinger and Letan , Shahidi and Shukla , Ghazani , Ghazani et al , Lechner et al , Mouloungui et al , Ferrari et al , Gogolewski et al , Alpaslan et al , Tasan et al , Verleyen et al , Prior et al , Koski et al , Schwartz et al , Tuberoso et al , Barrera‐Arellano et al , Souci et al , Lee et al , Martin‐Polvillo et al , Sundram et al , Yoshida et al , Basturk et al , Player et al , Rani et al , Gunstone , Delplanque , Medvedovici et al , Kamei et al , Mattila and Kumpulainen , Cai and Arntfield , Kozlowska et al , Naczk et al , Naczk et al , Naczk et al , Shahidi , Thiyam et al , Thiyam et al , Siger et al , Canibe et al , De Leonardis et al , Pedrosa et al , Kumar et al , Sakthivelu et al , Simonne et al , Tsukamoto et al , Wang and Murphy , Wang and Murphy , Xu and Chang , Xu and Chang , Codex Alimentarius International Food Standard , Haiyan et al , De Leonardis et al .…”
Section: Micronutrients Present In Rape Sunflower and Soybean Seedsmentioning
confidence: 99%
“…Sunflower oil is the fourth oil most produced in the world and its composition has a high potential to be improved for nutritional and industrial purposes through genetically selection and breeding of seeds (Mouloungui et al, 2006;Merah et al, 2012). The total sterol content of sunflower oil has been reported to range between 3000 and 4000 mg/kg, being the content of free sterols (62.4%) higher than that of the esterified forms (37.6%) (Verleyen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…O óleo é de excelente qualidade, e reconhecidamente utilizado por suas propriedades medicinais, sendo a cultura ainda usada pela fauna melífera, produção de silagem e forragem, adubação verde, melhoradora do solo e ornamental (UNGARO et al, 2009). Os fitoesteróis, presentes nos aquênios, relativamente, em altas concentrações, têm sido estudados pela sua grande importância alimentar e industrial (FOLMER, 2003;MOREAU;WHITAKER;HICKS, 2002;MOULOUNGUI;ROCHE;BUONIOLS, 2006). Por sua capacidade de produção de óleo vegetal em diferentes condições edafoclimáticas, é uma das quatro oleaginosas recomendada para cultivo no Rio Grande do Sul (SILVA;FREITAS, 2008).…”
Section: Introductionunclassified
“…No caso do girassol, a interceptação de radiação solar afeta a produção das plantas nos diferentes estádios, sendo que no período de enchimento dos aquênios esta afeta tanto o peso e a concentração de óleo nos aquênios (ECHARTE et al, 2010), quanto à partição dos ácidos graxos do óleo e outros constituintes (IZQUIERDO et al, 2009), principais componentes de utilidade industrial (FOLMER, 2003;MOREAU;WHITAKER;HICKS, 2002;MOULOUNGUI;ROCHE;BOUNIOLS, 2006). Portanto, a escala mostrase como um importante instrumento de avaliação de dano foliar que posteriormente pode auxiliar nas estimativas de prejuízos na produção final da cultura.…”
Section: Introductionunclassified